Does China overinvest? Evidence from a panel of Chinese firms. - Ding, S; Guariglia, A; Knight, J (Department of Economics (University of Oxford), 2010)
This paper addresses the hotly-debated question: do Chinese firms overinvest? A firm-level dataset of 100,000 firms over the period of 2000-07 is employed for this purpose. We initially calculate measures of investment efficiency, which is typically negatively associated with overinvestment. Despite wide disparities across various ownership groups, industries and regions, we find that corporate investment in China has become increasingly efficient over time. However, based on direct measures of overinvestment that we subsequently calculate, we find evidence of overinvestment for all types of firms, even in the most efficient and most profitable private sector. We find that the free cash flow hypothesis provides a good explanation for China’s overinvestment, especially for the private sector, while in the sector, overinvestment is attributable to the poor screening and monitoring of enterprises by banks.